Modulators of the extracellular matrix and risk of anterior cruciate ligament ruptures. Issue 2 (February 2017) - Rahim, Masouda; Mannion, Sasha; Klug, Blake; Hobbs, Hayden; van der Merwe, Willem; Posthumus, Michael; Collins, Malcolm; September, Alison V.
Abstract: Objectives: The extracellular matrix (ECM) of ligaments continuously undergoes remodelling in order to maintain tissue homeostasis. Several key mediators of ECM remodelling were chosen for investigation in the present study. It is thought that polymorphisms within genes encoding signalling molecules may contribute to inter-individual variation in the responses to mechanical loading, potentially altering risk of injury. Design: A genetic association study was conducted on 232 asymptomatic controls (CON) and 234 participants with surgically diagnosed anterior cruciate ligament (ACL) ruptures; of which 135 participants reported a non-contact mechanism of injury (NON subgroup). Methods: All participants were genotyped for ten variants in eight genes encoding ECM remodelling proteins. Haplotypes and allele combinations were also inferred. Results: The CASP8 rs3834129 ins allele was significantly over-represented in the male CON group compared to the male NON subgroup (p = 0.047, OR: 1.46, 95% CI: 1.01–2.12). In female participants, the IL1B rs16944 TT genotype was significantly under-represented in the CON group compared to the NON subgroup (p = 0.039, OR: 3.06, 95% CI: 1.09–8.64). Haplotype analysis revealed an under-representation of the CASP8 rs3834129-rs1045485 del-G haplotype in the CON group compared to both the ACL group (p = 0.042; haplo.score:2.03) and the NON subgroup (p = 0.037; haplo.score:2.09). Furthermore, following a pathway-based approach, genetic variants involved in the cell signalling cascade were associated with ACL injury risk. Conclusions: The novel independent associations and allele combinations observed implicate the apoptosis and cell signalling cascades as potential contributors to ACL injury susceptibility. Furthermore, these genetic variants may potentially modulate ECM remodelling in response to loading and ultimately contribute to ligament capacity.